2018
DOI: 10.3389/fonc.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapies for Human Epidermal Growth Factor Receptor 2-Positive Metastatic Breast Cancer Patients

Abstract: The median survival of patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) has more than doubled, since the discovery of HER2-targeted treatments: it rose from less than 2 years in 2001 (prior introduction of trastuzumab) to more than 4 years in 2017. The initial generation of HER2-targeted therapies included trastuzumab with taxanes in the first line, followed by the addition of lapatinib and by a switch to another cytotoxic agent after progression. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 173 publications
(240 reference statements)
0
67
0
4
Order By: Relevance
“…Resistance can be "intrinsic" or "upfront", i.e., cancer cells do not respond to therapy from the outset. Many cancer diseases, however, initially respond well to therapy, but after a temporary response resistant cancer cells emerge leading to "acquired" resistance, ultimately resulting in therapy failure and patient death [8][9][10][11][12][13][14][15][16][17][18][19] . Hence, cancer diseases that have become resistant to the available treatment options represent an unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance can be "intrinsic" or "upfront", i.e., cancer cells do not respond to therapy from the outset. Many cancer diseases, however, initially respond well to therapy, but after a temporary response resistant cancer cells emerge leading to "acquired" resistance, ultimately resulting in therapy failure and patient death [8][9][10][11][12][13][14][15][16][17][18][19] . Hence, cancer diseases that have become resistant to the available treatment options represent an unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…Other trials have shown that dual therapy with trastuzumab and a second anti-HER2 agent can lead to superior HER2 signalling blockage and better patient outcome in the neoadjuvant and advanced settings [70][71][72][73]. Research continues to study other anti-HER2 agents such as the pan-HER inhibitor neratinib or HER2-targeted drug delivery and immunotherapy [74].…”
Section: Human Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Patients with HER2+ MBC can also benefit from targeted treatment, with median survival having more than doubled since the advent of anti-HER2 therapy [74]. The current treatment consensus includes the use of multiple lines of HER2-targeted therapy beyond progression, often using dual blockade with trastuzumab and pertuzumab combined with chemotherapy as first line therapy, followed by treatment with different anti-HER2 agents.…”
Section: Biological Challenges: Temporal Heterogeneity and Resistancementioning
confidence: 99%
See 2 more Smart Citations